2013
DOI: 10.1159/000357669
|View full text |Cite
|
Sign up to set email alerts
|

Different Ratios of Bone Marrow Mesenchymal Stem Cells and Chondrocytes Used in Tissue-Engineered Cartilage and Its Application for Human Ear-Shaped Substitutes in vitro

Abstract: The application of chondrocyte-based cartilage tissue engineering is limited because of the lack of autologous cartilage sources and chondrocyte dedifferentiation after in vitro expansion. Coculture of bone marrow mesenchymal stem cells (BMSCs) and chondrocytes has been a promising strategy for cartilage engineering as chondrocytes can provide a chondrogenic environment for BMSCs. However, there are no systematic comparison studies for engineered cartilage constructed using different mixing ratios of BMSCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Tissue engineering has provided a promising perspective in the field of auricular reconstruction (Shieh et al ., ). The feasibility and efficacy to construct a cartilaginous tissue in the shape of human ear using tissue engineering technique have been successfully demonstrated by several groups (Kang et al ., ; Liu et al ., ; Pomerantseva et al . ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering has provided a promising perspective in the field of auricular reconstruction (Shieh et al ., ). The feasibility and efficacy to construct a cartilaginous tissue in the shape of human ear using tissue engineering technique have been successfully demonstrated by several groups (Kang et al ., ; Liu et al ., ; Pomerantseva et al . ; Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering has provided a promising perspective in the field of auricular reconstruction (Shieh et al, 2004). The feasibility and efficacy to construct a cartilaginous tissue in the shape of human ear using tissue engineering technique have been successfully demonstrated by several groups (Kang et al, 2013;Liu et al, 2010;Pomerantseva et al 2016;Zhou et al, 2011). The seed cells applied in previous studies included physiological chondrocytes derived from auricular, articular, nasal septum, and costal cartilage sources (Isogai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…31 Researchers have also demonstrated that minimum 20−30% of chondrocytes are required in co-culture ratios in order to produce cartilage tissue with good shape retention and for induction of stem cell differentiation. 32 Herein, our ultimate goal was to achieve equal or better chondrogenesis than chondrocytes alone while minimizing the load of chondrocytes, which are highly differentiated cells and difficult to isolate in desired numbers. Therefore, these abovementioned ratios were utilized in our study for reducing the chondrocyte number by replacement with the alternative cell source, MSCs, with the aim to achieve equal or even better chondrogenesis than chondrocytes.…”
Section: ■ Discussionmentioning
confidence: 95%
“…To address the issue of terminal ossification of MSCs, the co-culture of MSCs with mature chondrocytes has been investigated and found to be effective in generating phenotypically stable cartilage in the subcutaneous implantation site for the regenerated auricle (Zhang et al 2014). Besides phenotype maintenance, co-culturing can effectively reduce the quantity demand for chondrocytes, which are limited in supply, while exert the merit of MSCs which are more readily available (Kang et al 2013;Zhang et al 2014). Kang et al found that a co-culture arrangement of 30% chondrocytes and 70% BMSCs could generate ear-shaped cartilage in vitro (Kang et al 2013).…”
Section: Co-culture Of Chondrocytes With Mscsmentioning
confidence: 99%
“…Besides phenotype maintenance, co-culturing can effectively reduce the quantity demand for chondrocytes, which are limited in supply, while exert the merit of MSCs which are more readily available (Kang et al 2013;Zhang et al 2014). Kang et al found that a co-culture arrangement of 30% chondrocytes and 70% BMSCs could generate ear-shaped cartilage in vitro (Kang et al 2013). Zhang et al reported the generation of stable subcutaneous human earshaped cartilage engineered through co-culturing of a 30% human microtia chondrocytes with 70% human BMSCs in a nude mouse model (Zhang et al 2014).…”
Section: Co-culture Of Chondrocytes With Mscsmentioning
confidence: 99%